Patients' judgments of the importance of treatment-induced reductions in symptoms of depression: The role of specific symptoms, magnitudes of change, and post-treatment levels. (3rd April 2022) - Kim, Thomas T.; Xu, Colin; Derubeis, Robert J.
Abstract: Objective: An implicit assumption in the use of depressive severity measures to assess change during treatment, such as the Hamilton Rating Scale for Depression (HRSD), is that reductions from pre- to post-treatment that are equal to each other are of equal value. However, stakeholders' valuations of changes might depart substantially from this assumption. Method: Vignettes were constructed that reflected the six possible 1, 2, and 3-point reductions on five cognitive and four somatic symptoms derived from the HRSD. Former or currently depressed patients provided judgments of the importance of the symptom reductions. Mean importance ratings were modeled using symptom category and the pre/post-treatment combination. Differences were explored using the Tukey method. Results: Results indicated that mean ratings, from most to least important, were: Anxiety, Suicide, Depressed Mood, Work, and Guilt (the cognitive symptoms) followed by Somatic, Sleep, Appetite & Weight, and Retardation (the somatic symptoms). Participants valued reductions that resulted in posttreatment scores of zero more than expected, given the magnitude of the reductions. Conclusions: The value of reductions in symptoms captured by the HRSD, as judged by patients, appears to differ as a function of symptom category and the post-treatment score. Similar patterns might characterize other measures of depression severity.